Assessing the ecological effects of imidazolium hydrogen sulfate and morpholinium tetrafluoroborate ionic liquids on mixed culture growth - Nurul Aliaa, Rahman; Syamsul Bahari, Abdullah; Salwani, Md Zain; Ahmad Salihin, Samsudin; Suhaila, Omar; Mohamad Azmi, Bustam; Roshanida, A. Rahman; Alamin, Idris; Wan Mohd Hafizuddin, Wan Yussof (John Wiley & Sons, Inc., 2025)
Nowadays, ionic liquids (ILs) have extensive applications in biotechnology and are classified as green solvents. However, there are significant concerns over the effect of ILs on microorganism growth, especially towards mixed microorganisms. This study sets out to investigate the effect of synthesized ILs, particularly imidazolium hydrogen sulfate [IM][HSO4] and morpholinium tetrafluoroborate [MOR][BF4], towards mixed culture microorganisms, mainly identified as Bacillus cereus, Bacillus thuringiensis, and Pseudallescheria boydii. The toxicity effect of both ILs is assessed through the disk diffusion method. Moreover, the ecological effects of mixed culture growth on ILs are analyzed by conducting the growth inhibition test in fermentation liquid media. This study reveals that the growth of mixed culture microorganisms started to decline after 4 and 5 h of injecting the [IM][HSO4] and [MOR][BF4], respectively. This shows that mixed culture microorganisms have a longstanding growth and the least inhibition effect after being exposed to [MOR][BF4] rather than [IM][HSO4]. Similar findings are observed regarding the inhibitory effects, with [MOR][BF4] showing a smaller inhibition zone compared to [IM][HSO4]. This finding clearly indicates that imidazolium based ILs are more toxic than morpholinium based ILs. The present study lays the groundwork for further experimental investigation on [MOR][BF4] towards mixed culture microorganisms through the structural characteristics, explicitly focusing on using ILs without the alkyl chain.